Serum Vitamin D Level in Patients Undergoing Coronary Artery Catheterization - Nepal, Bikash; Sah, Ajit; Karki, Biplave; Ghimire, Jeet Prasad; Mahaseth, Aditya; Pandit, Swapnil; Sah, Ajit; Uranw, Surendra; Pandey, Naveen Kumar; Shah, Prashant; Karki, Prahlad (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: Vitamin D deficiency may be a risk factor for coronary artery disease (CAD). We aimed to measure the prevalence of vitamin D deficiency in CAD and its association with severity of angiographic proven CAD.Methods: This prospective, cross-sectional study included 106 consecutive patients who were admitted for typical angina and had signs of myocardial injury (ECG findings and/ or elevated troponin I or CK-MB) and who underwent coronary angiography at the university hospital of BPKIHS from August 2020 to April 2021. Patients were categorized into angiographic proven CAD group and angiographic normal coronary artery group. Serum vitamin D level was classified as normal (≥ 30 ng/ml) and deficiency (< 30 ng/ml).Results: Out of 106 patients, 78 patients (73.6%) had vitamin D deficiency and 28 (26.4%) had normal vitamin D level (p = 0.39). Vitamin D level (mean ± SD) in patients with angiographic normal coronary artery and angiographic proven CAD were 25.94 ± 11.63 ng/ml and 26.07 ± 12.90 ng/ml respectively (p = 0.97). Prevalence of vitamin D deficiency was 75.0% and 64.3% in significant CAD group and normal coronary artery group respectively (p = 0.39). Similarly, frequency of vitamin D deficiency were 68.6%, 78.3% and 88.90% in single, double, and triple vessel disease respectively (p = 0.21). The vitamin D level (mean ± SD) in single, double and triple vessel disease were 27.31 ± 14.02 ng/ml, 25.69 ± 12.72 ng/ml, 23.08 ± 9.45 ng/ml respectively.Conclusion: The prevalence of vitamin D deficiency in both angiographic normal coronary artery and angiographic proven CAD were high but comparable. There was no association of vitamin D deficiency with severity of angiographic proven CAD.